(untitled) (Plant Bulletin, 2025)
Jojoba (Simmondsia chinensis) is famous for its high-quality fixed oil production with various applications. Micropropagation is an efficient method for in vitro multiplication of plants. Thus, the present study aimed to explore an optimum medium for micropropagation of jojoba. Two experiments were conducted. In the 1st experiment, nodal explants of in vitro seedlings cultured on MS medium supplemented with 1,2,4,6,8 or 10 µM of each n6-benzyleaminopurine (BAP) or Kinetin (Kin) alone or in combinations (1+1+1, 2+2+1, 4+4+1, 6+6+2, 8+8+2, 10+10+2 µM) of BAP + Kin + IBA (indol-3-butyric acid) or NAA (α-naphthalene acetic acid) making up to 24 treatments, after 35 days of initial culture. Shoots obtained on optimum medium (OM) of the 1st experiment were selected for further cultivation of nodal (NS) and stub (SS, leftover shoot base 3 mm in size) explants in the 2nd experiment. Rooting was achieved ½ MS+4+4, 6+6, 8+8, 12+12 µM of IBA+NAA. Highest (91.12%) shoot induction with 16.63 number of shoots and 5.22 cm shoot length was obtained in the 1st experiment at 4+4+1 µM BA+Kin+IBA, considered as an OM. In the 2nd experiment, the rate of shoot induction was 100% from both SN and SS explants at 4µM BAP+4µM Kin+1µM IBA, respectively with 24.45 mean shoots and 6.56 cm shoot length were obtained from nodal explants after 35 days. Year-round data demonstrated 100% shoot induction during April-June on the above-mentioned combination of PGRs. Rooting frequency reached 55.20 %, with an average of 1.86 roots per shoot and 2.45 cm root length in ½ MS + 12 µM IBA + 12 µM NAA after 65 days. The rooted shoots were successfully acclimatized and grew well in the field.